1992
DOI: 10.3109/01902149209031680
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Experimental Acute Lung Injury 24 Hours After Exogenous Surfactant Instillation

Abstract: Subcutaneous injection of N-nitroso-N-methylurethane (NNNMU) produces an acute lung injury mimicking the adult respiratory distress syndrome. NNNMU-injured rats treated with intratracheal Survanta, 100 mg phospholipid/kg body weight, air, or normal saline were observed for 24 h. Twenty-four hours after treatment survival among Survanta-treated rats was significantly greater than for air- and saline-treated rats (9/15 vs. 2/15 and 3/15, respectively). The alveolar-to-arterial O2 gradient was lower in Survanta-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Comparison of air-and fluid-filled pressure volume profiles in isolated lungs of animals with experimental ARDS indicates that increases in static elastic recoil after acute inflammation are due to abnormalities in surfactant function and not to changes in tissue elastic recoil (13). An in vivo animal study (1) has demonstrated surfactant dysfunction after capillary leakage due to chemical injury. To date, the biochemical and biophysical processes that relate inflammation to alterations in surfactant function are not well understood.…”
mentioning
confidence: 99%
“…Comparison of air-and fluid-filled pressure volume profiles in isolated lungs of animals with experimental ARDS indicates that increases in static elastic recoil after acute inflammation are due to abnormalities in surfactant function and not to changes in tissue elastic recoil (13). An in vivo animal study (1) has demonstrated surfactant dysfunction after capillary leakage due to chemical injury. To date, the biochemical and biophysical processes that relate inflammation to alterations in surfactant function are not well understood.…”
mentioning
confidence: 99%
“…Many animal and clinical studies have demonstrated positive effects of either ESS alone or PLV alone on ALI induced by causes other than smoke inhalation (17)(18)(19)(20)(21)(22)(23)(24). Additionally, several studies with newborn or premature animals have shown the beneficial effects of a combined therapy of ESS and PLV on ALI induced by repeated saline lavage (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…A second disease for which administration of synthetic surfactant could be useful is ARDS [8,95]. (For a review, see Ref.…”
Section: Therapeutic Use Of Surfactantmentioning
confidence: 99%